Experimental paracoccidioidomycosis in the mouse. III. Histopathological and immunological findings after intravenous infection in the presence or absence of previous immunization - Maura Moscardi Bacchi; Marcello Franco (Revista da Sociedade Brasileira de Medicina Tropical, 1985)
Fifty male white Swiss mice aged 4 weeks were inoculated with 5 x 10(5) viable yeast forms of Paracoccidioides brasiliensis (strain 18). Ten of these animals had been previously immunized with particulate P. brasiliensis antigenfor 4 weeks by intradermal injection. The controls consisted of 10 animals that were only immunized and 10 animals submitted to no treatment. The animals were sacrificed 2, 4, 7,11 and 16 weeks later. We studied: 1) the anti-P. brasiliensis delayed hypersensitivity response measured by the footpad test 24 hours prior to sacrifice; 2) the specific antibody production measured by double immunodiffusion in agar gel; 3) the histopathology of lungs, liver, spleen, adrenals and kidneys. We observed that: a) the immunized animals developed more intense cell-immune responses than the infected ones; b) infection reduced the cell- immune response of the immunized animals; c) intravenous infection of mice with P. brasiliensis was characterized by a systemic and progressive granulomatous inflammation. The animals infected after previous immunization showed less extensive lung inflammation, with smaller granulomas and fewer fungi. The results indicate that the present murine model mimics some findings of the human subacute form of paracoccidioidomycosis (systemic disease with depressed cellular immunity) and that the extrapulmonary immunization scheme was able to induce a certain degree of protection of the lung from infection with P. brasiliensis